Uji Sensitivitas Amoksisilin dan Eritromisin terhadap Infeksi Sekunder dari Spesimen Pasien Infeksi Saluran Pernafasan Akut (Sensitivity Test of Amoxicillin and Erythromycin againts Secondary Infections from Acute Respiratory Infection Speciments) - Olyvia Yulyani Khaerul Putri; Cholis Abrori; Ida Srisurani Wiji Astuti (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Acute respiratory infections (ARI) is one of health problems in Indonesia, which are caused by viruses. But on a visit to health facility, physicians prescribe antibiotics as therapy. Irrational prescribing of antibiotics led to bacterial resistance. The use of amoxicillin and erythromycin as the first and second line drugs in patients with ARI causes high resistance to them. This study aimed to determine differences sensitivity of amoxicillin and erythromycin against secondary infection of ARI. This was a descriptive analytical study, using Mann-Whitney different test and determination of Minimum Inhibitory Concentration (MIC) antibiotics using logarithmic regression. The sample was obtained from specimens of patient ARI with secondary infection who visited UPT Pelayanan Kesehatan Universitas Jember. Five of twenty two specimens successfully cultured in Blood Agar Plate (BAP). The cultures showed five bacteria with Gram-positive cocci morphology and two with Gram-negative bacilli morphology. Mann-Whitney test showed significant difference between two drugs (p=0.008), where 85% bacteria were resistant to amoxicillin and 40% were to erythromycin. Logarithmic regression results, obtained amoxicillin’s MIC was 7.48-9.02 mg/L and erythromycin’s was 0.23-4.95 mg/L. It can be concluded, there was a significant difference between two drugs, where bacteria that cause secondary infections are no longer sensitive to amoxicillin. Keywords: Amoxicillin, Erythromycin, ARI